Levels of Chromium in Air with Chromium in the Blood of Workers Electroplating in Purbalingga - Hana Eka Rizky; Jojok Mukono (JURNAL KESEHATAN LINGKUNGAN, 2017)
Chromium (VI) is a form of chromium which commonly used in metal plating industry with engineering electroplating. The negative impacts for workers when contact with chromium are, skin irritation, nose, throat and lungs irritations. Research purposes are to describe the levels of chromium in the air and the blood of electroplating workers. This was an observational research design with cross sectional approach. Data analyzed by descriptive methods. Population of this research were electroplating workers of metal plating industry in Purbalingga. The samples were consisted of the respondents and environmental samples. The number of respondents were 8 workers which determinated purposive sampling methods. Environmental samples were obtained by measurements the levels of chromium in the air. The results showed that average level of chromium in the air 0.01 mg/m3. This level was appropriate to threshold limit value according to Peraturan Menteri Tenaga Kerja Dan Transmigrasi RI 13/MEN/X/2011. Most of electroplating workers (87.5%), had the high levels of chromium blood (1.7 Î¼g/L) and exceeded the normal limit value. Metal coating business owners should regularly control the use of personal equipment for workers to reduce the exposure of chromium for them.